Diplomatic relations of Russia with China and Japan at the beginning of the 19th century - Diyora Dilshodovna Azamova; Mexrangiz Qodiljonovna Tolibova (Science and Education, 2026)
At the beginning of the 19th century, Russia made many successful foreign policy actions. Through his diplomacy with surrounding countries, he first approached them and then colonized them all at once. Relations with Japan and China are of particular importance in such processes. Since relations with Japan were severed due to the intervention of England and the United States in the affairs of the Far East, this led to a rapprochement with China and the formation of an alliance. This topic provides valuable information about Russian diplomacy with China and Japan at the beginning of the 19th century. Even in the 19th century, Russia actively continued the policy of expanding the territory of the empire and exerting its influence on the surrounding countries, which began from the time of Peter I.